A Ten-year Retrospective Study of Tetanus at a Teaching Hospital in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2007)
Aims: To study the demographic, clinical features, treatment as well as outcomes of tetanus patients in the Bangladeshi population from 1994 to 2003. Design: A retrospective descriptive study. Setting: A large public Medical college hospital with a regional as well as referral service. Materials and Methods: All cases of tetanus in adult patients from January 1994 to December 2003 were identified from the medical record at the hospital and these were then retrospectively reviewed. Results: A total of 80 cases of tetanus were seen at the Faridpur Medical college hospital in the 10 years period with a mean of 8 cases per year. There were 55 male (68.75%) and 25 female (31.25%) patients. The mean age of the study population was 51.7±10.08 years. Most cases occurred in the age group of 60-69 years. Risk factor analysis revealed identifiable acute injury (puncture, prick/laceration) in 85%, CSOM (2.5%), surgery (2.5%), abortion (2.5%), skin ulcer (1.25%), burn (1.25%), child birth (1.25%), boil (1.25%). Thirty-two (40%) patients had medical wound care before hospital admission but none received tetanus immunoglobulin despite the absence of tetanus immunity. All the patients had the generalized type of disease. Body stiffness, trismus and dysphagia were the three commonest presenting complaints. All the patients with injury and wound (74/80) had their wound debrided. All the tetanus patients (80/80) received intravenous diazepam infusion as part of their management. Seventy two (90%) patients received intravenous crystalline penicillin. Sixty-five (81.25%) patients received intramuscular human antitetanus immunoglobulin and fourteen (17.5%) had tracheostomy performed. Inhospital complications were observed as respiratory (80%), cardiovascular (65%), gastrointestinal (57-5%), renal (33.37%), neurological (17.%) and others (22.5%). There were eighteen deaths in hospital, accounting for overall mortality of 22.5% (18/80). Higher mortality were observed in age group above 50 years than the age group below 50 years (29.16% vs 12.5%, P